2016
DOI: 10.3354/esr00756
|View full text |Cite
|
Sign up to set email alerts
|

Influence of human footprint and sensory disturbances on night-time space use of an owl

Abstract: Artificial sensory disturbances (sound and light) can extend far beyond the physical footprint of human development. Nocturnal predators such as owls may be influenced by artificial sound and light, as they depend on aural and visual cues when hunting. Owl nocturnal movements may also be altered by physical changes to the landscape, as these can affect prey availability. The burrowing owl population in Canada has declined by 90% and was classified as endangered in 1995. We tracked adult male burrowing owls Ath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 65 publications
1
14
0
Order By: Relevance
“…However, owls are unlikely to vocalize while hunting, so it is not likely we detected them in noisy areas while they were trying to hunt. A study tracking western Burrowing Owls with transmitters found that nocturnal space-use was not affected by industrial noise (Scobie et al 2016). Future research tracking these three species of owls found in the boreal forest will be necessary to understand how these species' behavior and movement is influenced by noise sources.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, owls are unlikely to vocalize while hunting, so it is not likely we detected them in noisy areas while they were trying to hunt. A study tracking western Burrowing Owls with transmitters found that nocturnal space-use was not affected by industrial noise (Scobie et al 2016). Future research tracking these three species of owls found in the boreal forest will be necessary to understand how these species' behavior and movement is influenced by noise sources.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing industrial noise levels negatively affect the hunting success of Northern Sawwhet Owls (Aegolius acadicus; Mason et al 2016), and reduce the foraging efficiency of Long-eared Owls (Asio otus) and Shorteared Owls (Asio flammeus; Senzaki et al 2016). However, a study on the nocturnal space use of Western Burrowing Owls (Athene cunicularia hypugaea) found they did not avoid areas affected by anthropogenic noise (Scobie et al 2016). A study on Spotted Owls (Strix occidentalis) found they will flush from nests more frequently with increased proximity to a noise source (Delaney et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Means (log-transformed ratios), standard error (SE) and t-test results for pairwise comparison of cover types available to juvenile owls are presented. Significance was determined at P value 0.05. importance of ecotones in agricultural landscapes for Burrowing Owls, possibly due to increased prey abundance and biomass in agriculture habitats (Rich 1986, Haug and Ophilant 1990, Leptich 1994, Moulton et al 2006, Marsh et al 2014a, Scobie et al 2016.…”
Section: Discussionmentioning
confidence: 99%
“…Owls nesting in highly agricultural areas used this habitat in proportion to its availability, whereas other owls appeared to seek out this habitat type. Other studies have found extensive use of agriculture by Burrowing Owls but agriculture made up a large portion of available land-cover types (Haug and Oliphant 1990, Sissons et al 2001, Gervais et al 2003, Marsh et al 2014a, Scobie et al 2016. In these situations, owls often either used this land classification in relation to availability (Gervais et al 2003) or Figure 1.…”
Section: Comparisonmentioning
confidence: 97%
See 1 more Smart Citation